2000
DOI: 10.1067/mhj.2000.101489
|View full text |Cite
|
Sign up to set email alerts
|

Sex and other predictors of intra-aortic balloon counterpulsation[ndash ]related complications: Prospective study of 1119 consecutive patients

Abstract: The current complication rate associated with IABC remains significant. Advances in IAB technology need to focus on the high-risk subset of patients that includes women, smaller patients, and those with peripheral vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In addition, there were very few complications, and all of these were amenable to treatment with surgical and endovascular methods. The 7.1% major vascular complications and 11.9% minor complications attending the use of the StarClose device are similar to the 15% vascular complications (11% were major) reported for conventional manual compression [12,13]. Hence, it can be deduced that the StarClose device was not inferior to standard manual compression in terms of safety and efficacy.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, there were very few complications, and all of these were amenable to treatment with surgical and endovascular methods. The 7.1% major vascular complications and 11.9% minor complications attending the use of the StarClose device are similar to the 15% vascular complications (11% were major) reported for conventional manual compression [12,13]. Hence, it can be deduced that the StarClose device was not inferior to standard manual compression in terms of safety and efficacy.…”
Section: Discussionsupporting
confidence: 72%
“…The most frequent vascular complication associated with IABP insertion was limb ischemia which had an incidence ranging from 0.9% to 26.7% (mean 8.03 ± 7.4). 12 – 16 , 18 29 Arceo et al concluded that limb ischemia occurred early after balloon placement and observed ischemia in 12 (5.7%) patients. In half of these patients, the ischemia was transient and resolved itself after removal of the IABP.…”
Section: Resultsmentioning
confidence: 99%
“… 18 In five studies, amputation for limb ischemia was reported at rates varying from 0.1 to 3.5%. 14 , 16 , 19 , 24 , 28 …”
Section: Resultsmentioning
confidence: 99%
“…Peripheral vascular disease, female gender, and diabetes mellitus are significant predictors,[ 7 ] and demonstrated a high rate of vascular complications in post-surgical patients (26%). [ 9 10 11 ] In our case, the patient was male, neither hypertensive nor diabetic. The probable cause in this patient was bleeding during insertion resulting in thrombus formation leading to limb ischemia.…”
Section: Discussionmentioning
confidence: 64%